Molecular correlates of cerebellar mutism syndrome in medulloblastoma. Issue 2 (23rd August 2019) - Jabarkheel, Rashad; Amayiri, Nisreen; Yecies, Derek; Huang, Yuhao; Toescu, Sebastian; Nobre, Liana; Mabbott, Donald J; Sudhakar, Sniya V; Malik, Prateek; Laughlin, Suzanne; Swaidan, Maisa; Al Hussaini, Maysa; et al.
Abstract: Background: Cerebellar mutism syndrome (CMS) is a common complication following resection of posterior fossa tumors, most commonly after surgery for medulloblastoma. Medulloblastoma subgroups have historically been treated as a single entity when assessing CMS risk; however, recent studies highlighting their clinical heterogeneity suggest the need for subgroup-specific analysis. Here, we examine a large international multicenter cohort of molecularly characterized medulloblastoma patients to assess predictors of CMS. Methods: We assembled a cohort of 370 molecularly characterized medulloblastoma subjects with available neuroimaging from 5 sites globally, including Great Ormond Street Hospital, Christian Medical College and Hospital, the Hospital for Sick Children, King Hussein Cancer Center, and Lucile Packard Children's Hospital. Age at diagnosis, sex, tumor volume, and CMS development were assessed in addition to molecular subgroup. Results: Overall, 23.8% of patients developed CMS. CMS patients were younger (mean difference −2.05 years ± 0.50, P = 0.0218) and had larger tumors (mean difference 10.25 cm 3 ± 4.60, P = 0.0010) that were more often midline (odds ratio [OR] = 5.72, P < 0.0001). In a multivariable analysis adjusting for age, sex, midline location, and tumor volume, Wingless (adjusted OR = 4.91, P = 0.0063), Group 3 (adjusted OR = 5.56, P = 0.0022), and Group 4 (adjusted OR = 8.57 P = 9.1 × 10 −5 ) tumors were found to be independently associated with higher risk of CMS compared with sonic hedgehog tumors. Conclusions: Medulloblastoma subgroup is a very strong predictor of CMS development, independent of tumor volume and midline location. These findings have significant implications for management of both the tumor and CMS.